Effect of Resected Gastric Volume on Postoperative Excess Body Weight Loss after Laparoscopic Sleeve Gastrectomy (Journal of Fatima Jinnah Medical University, 2024)
Background: Laparoscopic sleeve gastrectomy (LSG) is an effective bariatric procedure for achieving weight loss and improving obesity-related comorbidities. While the resected gastric volume (RGV) is thought to influence weight loss outcomes, its precise role remains uncertain. This study aimed to evaluate the relationship between RGV and % excess body weight loss (%EBWL) six months post-LSG.Patients and Methods: This prospective cross-sectional study was conducted in the General Surgery Department at Shifa International Hospital, Islamabad, from June 2023 to June 2024. Adult patients undergoing primary LSG were included, excluding those with prior bariatric surgery or incomplete follow-up data. Data collected included demographics, comorbidities, pre- and postoperative BMI, RGV, and %EBWL. RGV was measured intraoperatively by creating a gastrotomy at the antral end of the resected stomach, filling it with water via a Toomey syringe until maximum capacity, and measuring the volume in a graded container. %EBWL was calculated as [(initial weight − postoperative weight) ÷ (initial weight − ideal weight)] × 100. Procedures were performed by experienced surgeons, and patients were followed up for six months.Results: Among 41 patients (mean age 35.3 ± 12.9 year) 51% (21) were male and 49% (20) were female, mean preoperative BMI was 40.9 ± 7.3 kg/m², decreasing to 32.9 ± 5.7 kg/m² postoperatively. Comorbidities included diabetes (49%), hypertension (41%), and sleep apnea (73%). Mean RGV was 891.8 ± 187.6 mL, and mean %EBWL was 52.1 ± 31.1%. A weak, inverse correlation between RGV and %EBWL (r = -0.085, p = 0.793) was observed, indicating no significant association.Conclusion: The findings suggest that RGV does not significantly predict short-term weight loss after LSG. Further research is needed to explore other determinants of weight loss, including patient characteristics and postoperative behaviors.
Keywords: Laparoscopic sleeve gastrectomy; resected gastric volume; excess body weight loss.